Legis Ratio Norms Article 64 of Law No. 1 Year 2004 Concerning State Treasure - Pakpahan, Alman P.; Sudarsono, Sudarsono; Noerdajasakti, Setiawan; Permadi, Iwan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Article 64 paragraph (1) and paragraph (2) of Law no. 1 of 2004 concerning the State Treasury, states firmly that the Treasurer and other officials who have been determined to compensate the state/regional losses in settlements with the dimensions of State Administrative Law may still be subject to administrative sanctions and/or criminal sanctions. And if the treasurer and other officials are processed under criminal law, the criminal decision does not relieve the claim for compensation that has been determined through a settlement with the dimensions of State Administrative Law. Such norms are regulated in Article 64 paragraph (1) and paragraph (2) of Law no. 1 of 2004 concerning the State Treasury, of course, has the purpose and intent (ratio legis) of the legislators. Based on research on the minutes of the discussion of the Draft Law no. 1 of 2004 concerning the State Treasury, the legislative ratio of Article 64 paragraph (1) and paragraph (2) in general is 3 (three), namely: as a form of official accountability in carrying out office functions, punishment for Treasurers and Other Officials who are detrimental to State/Regional finances, and realizing the principle of returning State/Regional losses.